Forests for sustainable diets - poster - Hermanowicz, E.; Vinceti, B.; Bioversity International (2014)
Forests and trees play a key role in many food systems. Directly, they provide people with nutritious foods, and indirectly they provide ecosystem services and income. Food from trees and forests will be increasingly important in the face of challenges from population growth and climate change. Bioversity is currently working on three projects focusing on food tree species in Sub-Saharan Africa